Elastic wave propagation : proceedings of the second I.U.T.A.M.-I.U.P.A.P. Symposium on Elastic Wave Propagation, Galway, Ireland, March 20-25, 1988 - McCarthy, M. F. (Matthew F.); Hayes, M. A. (Michael A.) (North-Holland series in applied mathematics and mechanics, 1989)
This volume contains a timely collection of research papers on the latest developments in the ever-increasing use of elastic waves in a variety of contexts. There are reports on wave-propagation in various types of media: in both isotropic and anisotropic bodies; in homogeneous and inhomogeneous media; in media with cracks or inclusions in random media; and in layered composites. The bulk of the papers are concerned with propagation in elastic media, but also included are viscoelastic, thermoelastic and magneto-electroelastic wave propagation, as well as waves in porous and piezo-electric bodie.